QOL-DIS: a new assessment in analysing the quality of life of persons with disabilities - Abd Aziz Alias,; Nurul Hanis Aminuddin Jafry,; Rohana Jani,; Wong, Mikkay Ei Leen (Penerbit Universiti Kebangsaan Malaysia, 2024)
Accessing and monitoring the quality of life (QoL) of persons with disabilities (PWDs) is crucial in improving their QoL. Therefore, a reliable instrument is needed for that purpose. PWDs globally demand to get involved with anything related to their affairs, as stated in the movement slogan, “Nothing about us, without us”. The WHOQOL-DIS is the instrument developed by WHO and is used widely to assess the QoL of PWDs. However, the computation method is based on the unweighted score. Hence, this study proposes an approach to assess QoL using an index based on a weighted score, which allows the PWDs to rate each item according to their expectation or level of importance. An index approach is based on the total of the cognitive and emotional reactions or experiences compared with the expectations. Robust tests, namely correlation analysis, and uncertainty and sensitivity analysis, were conducted to check the robustness of the index approach. The findings showed that an index approach is reliable in the WHOQOLDIS instrument to assess the QoL of PWDs. Nevertheless, the QoL score between the index approach and the initial method only shows significant differences in the environment and discrimination domain. Besides, this study also suggests having a ten-point Likert scale instead of a five-point Likert scale when assessing the QoL of PWDs using an index approach.